Improving the Effectiveness of Community Participation in Village Fund Program - Wisnu Hendrianto (Bappenas Working Papers, 2019)
After four years of implementation of the Village Fund Program, although there were concrete results from the implementation of programs such as the establishment of various basic infrastructures in many villages, the number of cases of misuse of village funds by village heads showed that there were still serious problems in the governance of program implementation and accountability. In many cases, this is due to the ineffective participation of the village community in implementing the program. There is no community participation at all, or even if the community participate, their inability to support the weak village governments in managing village funds properly has resulted in the ineffective implementation of programs and uncontrolled corruption. In this regard, there is a strong correlation of the level of competence and public education with the effectiveness of community participation. A better level of community knowledge will not only increase the level of community participation in the process of policymaking and the implementation of the program but also the quality of the policies made and the results of programs that affect the community. To implement the Village Fund Program effectively and to derive better results through more effective community participation, the Indonesian Government must focus its efforts on increasing community’s capacity to participate in program implementation both through formal and informal education or enhance the role of Non-Governmental Organizations in community empowerment.